On Soft b-w-Open Sets - Carlos Granados (IndoMS, 2021)
In this paper, we used the notion of soft w-open sets to introduce and study the concepts of soft b-w-open sets. Moreover, some of their properties are shown. Furthermore, the concepts of soft b-T1 and soft b-T2 spaces are defined.